The Dynamics of Shallot Price Fluctuations and Its Disparities in Indonesia - Sigit, Argadatta; Supartomo, Supartomo (Terbuka Journal of Economics and Business, 2023)
A agricultural product called shallots is frequently used to improve the flavor of Indonesian food. This ingredient is only required in trace amounts in a recipe, but price swings can fuel inflation, an ongoing economic disease in Indonesia. The purpose of this research is to analyze the dynamics of shallot price fluctuations in Indonesia and the disparities that may arise. Explanatory descriptive statistics were used to analyze secondary data from the National Strategic Food Price Information Center that was made available online for this research. Unless there are distortions that affect the economy and trade, such as the COVID-19 pandemic in 2020–2021, it appears from the research that the price of shallots fluctuates regularly and in a predictable pattern, with a price increase in the first quarter and a peak at the beginning of the second quarter each year. In provinces which produce shallots, there is a fairly significant price disparity because there are many businesses engaging in the shallot trading system and there are also numerous trade routes, which leads to perfect competition in the market and a relatively cheap base price for shallots. There aren't many shallot business actors in the provinces with a production deficit or importer status, so wholesalers who act as importers can control prices as in a monopoly market, and price disparities are kept small to prevent economic turmoil in the local community. However, the price difference is still fairly high on a per-unit basis.